2023
DOI: 10.1242/jcs.261265
|View full text |Cite
|
Sign up to set email alerts
|

Altered cohesin dynamics and H3K9 modifications contribute to mitotic defects in thecbf11Δlipid metabolism mutant

Abstract: Mitotic fidelity is crucial for the faithful distribution of genetic information into the daughter cells. Many fungal species, including the fission yeast Schizosaccharomyces pombe, undergo a closed form of mitosis, during which the nuclear envelope does not break down. In S. pombe numerous processes have been identified that contribute to successful completion of mitosis. Notably, perturbations of lipid metabolism can lead to catastrophic mitosis and the “cut” phenotype. It was suggested that these mitotic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…2). These results are consistent with our recent findings that, in addition to any issues with the production of new membranes, mitotic fidelity in lipid metabolism mutants is affected by changes in centromeric chromatin structure and cohesin dynamics [18]. While we did not detect any nitrogen-dependent improvement in mitotic NE dynamics and FA and lipid composition composition, we found that ammonium supplementation clearly normalised the timing of mitotic progression, restoring the duration of individual mitotic phases close to their WT state (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…2). These results are consistent with our recent findings that, in addition to any issues with the production of new membranes, mitotic fidelity in lipid metabolism mutants is affected by changes in centromeric chromatin structure and cohesin dynamics [18]. While we did not detect any nitrogen-dependent improvement in mitotic NE dynamics and FA and lipid composition composition, we found that ammonium supplementation clearly normalised the timing of mitotic progression, restoring the duration of individual mitotic phases close to their WT state (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, we previously showed that ammonium supplementation did not correct the aberrant lipid droplet (LD) content of Δcbf11 cells [26]. Also, we demonstrated that the defects in Δcbf11 mitosis manifest already before anaphase [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently described a requirement for Cbf11 in the maintenance of chromatin structure and genome integrity. Cells lacking intact Cbf11 are sensitive to the microtubule poison thiabendazole (TBZ), and to camptothecin (CPT), an inhibitor of topoisomerase II and a potent inducer of double-stranded DNA breaks (Marešová et al, 2024; Vishwanatha et al, 2023). We now tested whether Mga2 is also involved in these processes.…”
Section: Resultsmentioning
confidence: 99%